Primary plasmacytoma of the thyroid gland: a case report of a rare neoplasia - Cambruzzi,Eduardo (2012)
Extramedullary plasmacytoma comprises 3%-5% of all plasma cell neoplasms, and approximately 80% of the cases occur in the upper respiratory tract. Primary thyroid plasmacytomas (PTP) are rare tumors. The authors report a case of PTP in a male patient with dyspnea and dysphagia. Physical examination and computerized tomography (CT) scan revealed a solid tumor affecting the thyroid gland, measuring 12 cm in its greatest dimension. Surgical biopsy was performed. Microscopy revealed a hypercellular malignant neoplasm composed of round plasmacytoid cells arranged in solid nests, which showed a positive immunoexpression for CD138, epithelial membrane antigen (AME), kappa light chains and multiple myeloma oncogene 1 (MUM1). The diagnosis of PTP was accordingly established.